Kebijakan Hukum Pidana Dalam Pemberantasan Kejahatan Perdagangan Orang (Trafficing) - Sidqi Ferin Diana (UNISSULA Semarang, 2020)
Action which oppose against human being prestige and standing and impinge basic rights have been arranged in Law Number : 21 Year 2007 about Eradication Doing An Injustice Commerce People. Such action with refer to recruitment action, transportation, relocation, delivery, evacuation, or acceptance one with hardness threat, usage of hardness, abduction, prisoner both for conducted in inter-states and also state, for the purpose of exploitation or result people exploited, is to represent people commerce doing an injustice. Exploitation conducted with or without approval permission of victim covering but do not limited to prostitution, service or activity force, similar praktic or slavery of slavery. Recruitment, transportation, transfer of, acceptance or concealment a child for the purpose of exploitation have to be assumed